Campus to host First Amendment Celebration Dec. 6 - Uribes, Tom::::::::: (2013)
A First Amendment Celebration at Fresno State from 8:30 a.m.-3 p.m. Friday, Dec. 6, at the Satellite Student Union will feature keynote speaker Dr. Ken Paulson, former editor of USA Today, president of the First Amendment Center and dean of the College of Mass Communication at Middle Tennessee State University.